2009
DOI: 10.1021/jp810055q
|View full text |Cite
|
Sign up to set email alerts
|

Binding Energies of O2 and CO to Small Gold, Silver, and Binary Silver−Gold Cluster Anions from Temperature Dependent Reaction Kinetics Measurements

Abstract: A detailed analysis of experimentally obtained temperature-dependent gas-phase kinetic data for the oxygen and carbon monoxide adsorption on small anionic gold (Au(n)(-), n = 1-3), silver (Ag(n)(-), n = 1-5), and binary silver-gold (Ag(n)Au(m)(-), n + m = 2, 3) clusters is presented. The Lindemann energy transfer model in conjunction with statistical unimolecular reaction rate theory is employed to determine the bond dissociation energies E(0) of the observed metal cluster complexes with O(2) and CO. The accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
144
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(159 citation statements)
references
References 106 publications
15
144
0
Order By: Relevance
“…For modeling the transition state, the vibrational frequencies are taken to be the same as for the ground state structures minus the middle frequency that is treated as internal translation along the reaction coordinate, and two neighboring frequencies are scaled by a factor of 0.5. 13 Figure 1 displays the calculated unimolecular dissociation rate constants k d as a function of the applied laser photon energy for different dissociation pathways of Au 4 + , Au 3 Cu + , and Au 2 Cu 2 + (at T = 203 K). Due to the small size of the investigated clusters and their small number of available vibrational degrees of freedom, the unimolecular dissociation is much faster (typical 1-1000 ps) than the time-scale of our experiment (few tens of μs).…”
Section: B Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For modeling the transition state, the vibrational frequencies are taken to be the same as for the ground state structures minus the middle frequency that is treated as internal translation along the reaction coordinate, and two neighboring frequencies are scaled by a factor of 0.5. 13 Figure 1 displays the calculated unimolecular dissociation rate constants k d as a function of the applied laser photon energy for different dissociation pathways of Au 4 + , Au 3 Cu + , and Au 2 Cu 2 + (at T = 203 K). Due to the small size of the investigated clusters and their small number of available vibrational degrees of freedom, the unimolecular dissociation is much faster (typical 1-1000 ps) than the time-scale of our experiment (few tens of μs).…”
Section: B Data Analysismentioning
confidence: 99%
“…12) and anionic Au n Ag m − (n + m = 2, 3) (Ref. 13) toward carbon monoxide and molecular oxygen changes discontinuously with increasing silver content, which is also reflected in considerable differences of the cluster-molecule binding energies. 12,13 The optical properties of noble metal nanoparticles attracted a lot of attention, 14 not in the least because their UVvisible absorption spectrum is dominated by the presence of an intense surface plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%
“…7 In a very recent communication, Hamilton et al reported evidence of infrared driven surface chemistry of N 2 O on Rh + n clusters. 8 The adsorption of CO on pure gold [9][10][11][12] and silver [10][11][12] cluster cations and anions was investigated previously, revealing size specific CO saturations and the strongest binding energies of CO to positively charged gold clusters. In contrast, small negatively charged silver clusters exhibit no reactivity toward CO at all.…”
mentioning
confidence: 97%
“…In contrast, small negatively charged silver clusters exhibit no reactivity toward CO at all. 4,12,13 A thermal catalytic CO oxidation mechanism employing molecular oxygen was shown to proceed on free Au 2 − .…”
mentioning
confidence: 99%
“…This limit has been used in the reactions of small molecules with clusters trapped within a a quadrupole ion trap in the presence of buffer gas. [22][23][24][25][26] B.2 Data acquisition and analysis Data which describes the formation of Au10 COn + complexes is obtained by exposing trapped Au10 + clusters to CO at a constant helium background pressure for varying times. Mass spectra are obtained by ejecting the trapped ions into an ion detector.…”
Section: B1 Rate Equations For Kinetics Analysesmentioning
confidence: 99%